2003
DOI: 10.1093/nar/gkg742
|View full text |Cite
|
Sign up to set email alerts
|

Retrovirus silencer blocking by the cHS4 insulator is CTCF independent

Abstract: Silencing of retrovirus vectors poses a significant obstacle to genetic manipulation of stem cells and their use in gene therapy. We describe a mammalian silencer blocking assay using insulator elements positioned between retrovirus silencer elements and an LCRbeta-globin reporter transgene. In transgenic mice, we show that retrovirus silencers are blocked by the cHS4 insulator. Silencer blocking is independent of the CTCF binding site and is most effective when flanking the internal reporter transgene. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
62
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 34 publications
5
62
0
Order By: Relevance
“…(61) As a means of combating these negative viral elements, it has recently been demonstrated that the cHS4 insulator is able to block retroviral silencing in a murine stem cell virus (MSCV) vector in transgenic mice. (60) Interestingly, the results obtained with this MSCV retrovirus are in agreement with the data obtained previously in chicken stably transfected cell lines. (33,60) First, when two copies of the cHS4 core element are placed on each side of an LCR-b-globin transgene (Fig.…”
Section: Viral Vectors and Insulatorssupporting
confidence: 90%
See 1 more Smart Citation
“…(61) As a means of combating these negative viral elements, it has recently been demonstrated that the cHS4 insulator is able to block retroviral silencing in a murine stem cell virus (MSCV) vector in transgenic mice. (60) Interestingly, the results obtained with this MSCV retrovirus are in agreement with the data obtained previously in chicken stably transfected cell lines. (33,60) First, when two copies of the cHS4 core element are placed on each side of an LCR-b-globin transgene (Fig.…”
Section: Viral Vectors and Insulatorssupporting
confidence: 90%
“…(60) Interestingly, the results obtained with this MSCV retrovirus are in agreement with the data obtained previously in chicken stably transfected cell lines. (33,60) First, when two copies of the cHS4 core element are placed on each side of an LCR-b-globin transgene (Fig. 3), the highest protection against silencing is obtained, an effect that is translated to the most-elevated copy number and with homogeneous gene expression, again confirming that two copies of the 250 bp core insulator are as good as the two copies of the original 1.2 kb element (Fig.…”
Section: Viral Vectors and Insulatorssupporting
confidence: 90%
“…11,16 Previous attempts to incorporate insulators into recombinant viral vectors intended for gene therapy yielded reduced transgene expression variegation and limited chromosomal position effect. [17][18][19][20][21] Most of these studies were performed on gamma-retroviral and lentiviral vectors with the cHS4 insulator in various mouse and human cell types. 22 Implementation of the full-length, 1.2-kb element in gammaretroviral vectors was associated with reduced genotoxicity, but also with important constraints concerning vector design and titer of infectious particles, mainly owing to the substantial size of this sequence.…”
Section: Introductionmentioning
confidence: 99%
“…CTCF remains the only insulator-binding protein known to direct enhancer blocking in vertebrates. Despite CTCF's pivotal role in enhancer blocking, removal of the CTCF binding site has no effect on the barrier activity of HS4 [42,60]. The enhancer blocking and barrier to silencing properties are separable functions, and therefore employ different mechanisms.…”
Section: Lessons From Chicken Chromatin Boundariesmentioning
confidence: 99%
“…A role for CTCF elements in heterochromatin boundary formation is frequently posited, but conclusive evidence in support of this particular function is not available at present. The CTCF binding site of the chicken HS4 insulator is not required for its barrier activity [42,60]. Furthermore, the well characterized CTCF-mediated human H19 ICR and TCRA/D BEAD-1 enhancer-blocking elements also lack barrier activity [42].…”
mentioning
confidence: 99%